On the spectrum of a stationary problem with nonlocal integral type boundary condition - Pečiulytė, Sigita; Štikonienė, Olga; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2004)
We investigated a eigenvalue problem for simple second order ordinary differential equation with one integral type nonlocal boundary condition. The eigenvalues and eigenfunctions of such problem are depending on few parameters in the nonlocal boundary conditions. For some values of those parameters all eigenvalues are positive. We find conditions when there is one zero or one negative eigenvalue. We investigate similar discrete problem too.